ORGANIZATION OF COGNITIVE ACTIVITY OF CADETS - Menglieva, S.S. (Innovative Development in Educational Activities, 2024)
This article analyzes using traditional and non-traditional methods of teaching cadets at the military establishments. This article uses modern methods of teaching and training military personnel.